Supporting Third Year Medical Students' Skill Acquisition and Self-Efficacy with Coping Models and Process Feedback during Laparoscopic Knot Tying Simulation - Dempsey, Michael S.; Kauffman, Douglas F. (Frontiers in Psychology, 2017)
Background: During the third year general surgery clerkship, medical students are required to develop laparoscopic knot-tying skills. Knot-tying skills studies often rely on objective variables (e.g., time, materials used, number of iterations) that lend themselves to correlational analysis of pre- and post-intervention skill level. This study differs by examining how instructional interventions—role modeling and feedback—affect medical students’ skill acquisition and self-efficacy during a laparoscopic surgical simulation training session. Methods: Seventy-eight surgical clerkship students were assigned randomly to one cell of a 2X2 factorial design. Participants observed one of two types of role modeling (expert vs. coping) and received either process-oriented or outcome-oriented feedback during a 30-minute laparoscopic training session. Participants also completed several surveys that assessed their interest in surgery and their self-efficacy for laparoscopic knot tying. Results: Coping model groups tended to perform better on the knot tying task, though this was less the case in the presence of outcome feedback. Expert model groups slightly outperformed the coping model group on the peg transfer task, but in the presence of outcome feedback they reported the lowest satisfaction with their performance and the lowest self-efficacy for the knot tying task. The coping model combined with process feedback had a positive influence on students’ efficiency in learning the task, on their satisfaction with their performance, and on their self-efficacy for laparoscopic knot typing. Conclusions: Results are discussed relative to self-regulated learning theory.